Seed Bio-priming of wheat with a novel bacterial strain to modulate drought stress in Daegu, South Korea - Shaffique, Shifa; Imran, Muhammad; Kang, Sang-Mo; Khan, Muhammad Aaqil; Asaf, Sajjad; Kim, Won-Chan; Lee, In-Jung (Frontiers in Plant Science, 2023)
Abstract: Wheat is the major cereal food worldwide and has a key role in alleviating the global hunger crisis. Drought stress reduces crop yield by up to 50% globally. The use of drought-tolerant bacteria for biopriming can improve crop yields by countering the negative effects of drought stress on agronomy. Seed biopriming can reinforce the cellular defense responses to stresses via the stress memory mechanism; it activates the antioxidant system and induces phytohormone production. In present study, bacterial strains were isolated from rhizospheric soil around Artemisia plant, from Pohang beach, located near Daegu, South Korea. Seventy-three isolates were screened for their growth promoting attributes and biochemical characteristics. Among them, the bacterial strain SH-8 was preferred based on its plant growth promoting bacterial traits, which are as follows: ABA concentration = 1.08 ± 0.05 ng/mL, phosphate solubilizing index = 4.14 ± 0.30, and sucrose production = 0.61± 0.13 mg/mL. The newly isolate SH-8 significantly tolerated oxidative stress. Antioxidant analysis showed that SH-8 contained significantly higher levels of CAT, SOD, and APX. The present study also quantified and standardized the effect of biopriming wheat (Triticum aestivum) seeds with the newly isolate SH-8. SH-8 was significantly effective in enhancing drought tolerance by up to 20%, with 60% germination potential compared to that in the control group. The lowest drought stress severity and highest germination potential, SVI, and GE (90%, 2160, and 80%, respectively), were recorded with SH-8 biopriming. These results show that SH-8 enhances drought stress tolerance up to 20%. Our study suggest that the newly isolated rhizospheric bacterium SH-8 (gene accession number OM535901) is a valuable bio stimulant that improves drought stress tolerance in wheat and might be used as a biofertilizer under drought conditions.